CHET TILI DARSLARIDA O‘QISHNI O‘RGATISH («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
At the first stage of this article, the organization of a foreign language lesson is considered. It describes the procedure for organizing lessons for studying abroad and the tasks that need to be completed.
Keywords: reading, teaching a foreign language, text, perception, speech, indirect communication, intellectual development.